2011
DOI: 10.1007/s12011-011-8980-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progesterone, β-Estradiol, and Androsterone on the Changes of Inorganic Element Content in Barley Leaves

Abstract: The present study was performed to determine the changes in inorganic element content in barley leaves of mammalian sex hormones (MSH). Barley leaves were sprayed with 10(-4), 10(-6), 10(-9), 10(-12), 10(-15) M concentrations of progesterone, β-estradiol, and androsterone at 7th day after sowing. The plants were harvested at the end of 18 days after treatment with MSH solutions. The inorganic element concentrations were determined using wavelength dispersive X-ray fluorescence spectroscopy technique. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 4 publications
1
23
0
1
Order By: Relevance
“…LA remarkably increased the Ca content compared to control under stressed and unstressed conditions, whereas salt stress reduced markedly Ca content compared to control. The increase in Ca content has critical important in terms of resistance of plants, because Ca can reduce membrane damages by ensuring stability and continuity of membrane structure . In addition to its protective effect on membranes, Ca has also a pivotal signalling function such as direct inhibitory effect on a Na + entry system and a facilitative effect on K + entry system to maintain higher K + /Na + selectivity in response to salt stress .…”
Section: Discussionmentioning
confidence: 99%
“…LA remarkably increased the Ca content compared to control under stressed and unstressed conditions, whereas salt stress reduced markedly Ca content compared to control. The increase in Ca content has critical important in terms of resistance of plants, because Ca can reduce membrane damages by ensuring stability and continuity of membrane structure . In addition to its protective effect on membranes, Ca has also a pivotal signalling function such as direct inhibitory effect on a Na + entry system and a facilitative effect on K + entry system to maintain higher K + /Na + selectivity in response to salt stress .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of plants with steroid estrogens affects root and shoot growth (Hewitt and Hillman, 1980;Guan and Roddick, 1988b), pollination in flowers (Ylstra et al, 1995) and seed germination (Janeczko and Skoczowski, 2011). Interestingly, at the biochemical level, mammalian sex hormones (MSH) significantly improve the inorganic contents of barley, maize, chickpea and beans seeds (Dumlupinar et al, 2011;Erdal and Dumlupinar, 2011a;Erdal et al, 2012), and chlorophyll, carotenoid, sugar, and protein in lentil seed,duckweed, soybean and fennel (Czerpak and Szamrej, 2003b;Dumlupinar et al, 2011;Chaoui and El Ferjani, 2013;Sherafatmandjour et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mammalian sex hormones (MSHs) such as progesterone, β‐estradiol and androsterone, previously known to occur in only animals, are now isolated from various plant species and their tissues and organs; however, they have not been accepted as plant hormones, yet 9–11. These hormones12 are lipophilic and low molecular weight and play a key role in controlling the process of development and reproduction in mammals. Many studies have been carried out regarding their presence, quantities and mechanisms of action since they were first detected in plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the other study showed that although MSH treatment increased Na content in chickpea seedlings; it increased K and Ca contents and decreased Cl content. These reports are very important for their usability to counteract salt stress because MSHs prevented the change in favour of Na of K/Na and Ca/Na rates 10, 12, 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation